The methodology choice with analyzing cross-border mergers and acquisitions - Anita Maček; Rasto Ovin (Naše gospodarstvo/Our economy, 2012)
In this article the authors present methodological steps with the research for which statistical data are non-existent. At the same time, primary data from transaction participants are also not obtainable. The empirical phenomena were cross-border mergers and acquisitions. The article presents the original solution, which helped the authors avoid this problem. The simplicity of the innovative method was compensated for by using several statistical tests. Results were obtained using basic methods of statistical tests, which led to the conclusion that the estimation of stylized facts on the basis of the fundamental method (poll) was reliable enough.